Pain parameters for buffered and non-buffered anesthetic injections in children undergoing dental procedures - Theodora Erlin Puspitasari; Iwan Ahmad Musnamirwan; Kirana Lina Gunawan; Meirina Gartika (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2023)
Background: Dental procedures, such as injections, usually cause pain and make children uncomfortable and uncooperative. One approach for reducing pain is the use of buffered anesthetics. Purpose: The research objective was to assess the pain parameters between buffered and non-buffered anesthetic injections, based on oxygen saturation, pulse rate, and the self-reporting of pain by the children. Methods: The research method was quasi-experimental, with purposive sampling of 19 children. Pain parameters, based on oxygen saturation and pulse rate, were measured using a pulse oximeter. The self-reporting of pain used the Wong–Baker FACES® pain rating scale. Statistical analysis used a t-test and Mann–Whitney test with P < 0.01 taken as statistically significant. Results: The results showed a significant difference in oxygen saturation before and after the injection of buffered and non-buffered anesthetics (P = 0.0002). Delivering the buffered anesthetics were reported to be less painful than non-buffered anesthetics. The oxygen saturation and pulse rate were inversely proportional to the self-reporting of pain in children. Statistical analysis showed no significant difference between oxygen saturation (P = 0.5) and pulse rate (P = 0.4886) in those receiving buffered and non-buffered anesthetics. However, there was a significant difference in the self-reporting of pain between the two groups (P = 0.00000262). Conclusion: Pain parameters could be measured physiologically and psychologically. This research concludes that physiologically, there was no difference in pain parameters, based on oxygen saturation and children’s pulse rate. Psychologically, there was a difference in the self-reporting of pain; 14 children reported that delivering the buffered anesthetic was painless.